A new species of Profundulus (Cyprinodontiformes: Profundulidae) from southeastern Mexico - Sara Elizabeth Domínguez-Cisneros; Ernesto Velázquez-Velázquez; Omar Domínguez-Domínguez; Rosa Gabriela Beltrán-López (Neotropical Ichthyology)
Abstract A new species of Profundulus is described from several localities in the Grijalva river basin and rivers of the Isthmus of Tehuantepec, in southern Mexico, using a combination of morphological and molecular data. Genetically, it is separated from other Profundulus species analyzed by a minimum of 3.86% uncorrected p-distance for the nd2 mitochondrial gene. The new species can be distinguished from its congeners by the following combination of characters: presence of a set of large black spots on the scales on the sides of the body, a set of black spots whose size is equal to or greater than 50% of the diameter of the pupil in the new species, a larger number of scales on the lateral line and a larger number of predorsal scales. Based on the phylogenetic analysis of molecular sequence data, the new species is recovered close related to P. chimalapensis, supported by posterior probability of 0.96, and this clade was recovered close related to P. oaxacae, with a posterior probability of 1.0 and bootstrap support of 100. This is the twelfth member of the genus Profundulus.